Solution of the Bus Route Design Problem - Pribyl, Vladimir (Communications - Scientific Letters of the University of Zilina, 2009)
The paper deals with a single bus route design problem. It consists of two stages. The first one is to choose the set of stops fulfilling a defined constraint. The second one is the precising of the order of the stops on the route. Both exact and heuristic methods are proposed and verified on 9 randomly generated networks. Very high computational complexity of the exact method and some ways how to reduce it are discussed in the paper. Comparison of the experimental results is presented in the final table.
Keywords: bus; design; network; optimization; route; method; heuristics